El Excentrico, 1972-06-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
June 20, 1972 [20 de junio de 1972]. No volume or issue number. Cover has a group photograph of people in evening wear for Club San Felipe's 14th Anniversary Ball in San Jose